1980
DOI: 10.1007/bf00121611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing conditions and age on the difference in mating success between alcohol dehydrogenase genotypes of Drosophila melanogaster

Abstract: Multiple choice mating experiments were carried out with the alcohol dehydrogenase (Adh) genotypes FF and SS of Drosophila melanogaster. Rearing conditions and age of the flies were varied. The large mating advantage of FF for 4-6 days old flies, reared at 25°C, found by Pot et al. (1980), was confirmed. This advantage decreased or even disappeared when rearing temperature or age of the flies was lowered. The relative humidity during rearing also influenced mating success. The relevance of these results for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It has been known for a number of years that the mating success of a male is affected by its genotype (Petit & Ehrman, 1969; for allozyme genotypes see Knoppien et at., 1980;McKenzie & Fegent, 1980;. Maynard Smith (1956) has shown that females inseminated by ontbred males produce more offspring than those inseminated by inbred males.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for a number of years that the mating success of a male is affected by its genotype (Petit & Ehrman, 1969; for allozyme genotypes see Knoppien et at., 1980;McKenzie & Fegent, 1980;. Maynard Smith (1956) has shown that females inseminated by ontbred males produce more offspring than those inseminated by inbred males.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes this heterogeneity can wrongly suggest the occurrence of a rare type mating advantage. Little investigation has been done concerning the statistical distribution of mating success, but Knoppien, Pot & van Delden (1980) have shown that heterogeneity among runs was found in none out of six cases for males and in three out of six cases for females. In retesting the rare male mating advantage found by Ehrman ( I 967), O'Donald ( I 980 : pp.…”
Section: Peter Knoppienmentioning
confidence: 98%
“…The inconsistency sometimes seen in rare male experiments, judged by Bryant et al (1980) as witnessing the artificial nature of this phenomenon, can be explained otherwise. Because mating success of a given genotype in Drosophila is dependent on many factors (Spiess, 1970;Parsons, 1973;Knoppien et al, 1980) it seems difficult to keep all factors constant in any experiment dealing with mating success. Anderson & McGuire ( I 978), for instance, found statistically significant differences in mating success of a given genotype between two population cages, even though painstaking care had been taken to keep all factors equal in both cages.…”
Section: Peter Knoppienmentioning
confidence: 99%
“…However, demonstrations of the adaptive significance of such polymorphisms are mainly indirect (Lewontin, 1974;Koehn, 1978). In the case of the alcohol-dehydrogenase (Adh) locus in Drosophila, however, there is now substantial agreement that the differences between alleles at this locus can have adaptive significance in a number of species (Gibson, 1970;Clarke, 1975;David, 1977;Starmer et al, 1977;Fontdevila et al, 1980;Knoppien et al, 1980). Thus in D. melanogaster, the frequently reported clines in Adh allele frequencies apparently have a selective origin (Pipkin et aL, 1973), whereby one agent of selection is temperature, a temperature-correlated variable perhaps relating to resources, or a combination of the two (Malpica & Vassalo, 1980).…”
Section: Introductionmentioning
confidence: 99%